Imaging salmonella at a single cell resolution - Benkherouf, Alaa (My University, 2022)
Salmonella is a rod-shaped bacterium that infects many cells including macrophages in the gastrointestinal tract and causes salmonellosis. Single-cell technologies are being utilised to study the heterogeneity of host-pathogen interactions, which focus on unravelling the different experiences Salmonella goes through during infection within the same host. ADP-ribosylation is the process of transferring of ADP-ribose from NAD⁺ onto a target molecule and is catalysed by PARPs. PARPs have many roles including inflammation and host–pathogen interactions, yet it is hardly studied when comes to bacterial infections. It is involved in M1/M2 polarisation of macrophages, but on the other hand, Salmonella is known to favour M2 polarised macrophages for long term persistence. In an ongoing study in the host laboratory (TCML), PARP14 was found to be upregulated in Salmonella infected macrophages in vitro. The aim of this study is to optimise in vitro conditions to monitor Salmonella-macrophage interaction at a single cell resolution and the possible heterogeneity within. Subsequent aim is to determine the functional importance of ADP-ribosylation-mediated cell signalling processes to Salmonella-macrophage interaction using pharmaceutical inhibition of PARP-enzymes. Flow cytometry was employed to optimise the MOI of Salmonella SL1344-GFP and PARP inhibitor PJ34 concentration. For single-cell visualisation, epifluorescence microscopy was used. Automated batch image analysis was done using ImageJ macro that calculated the number of bacteria and cells per coverslip. A manual approach was implemented to calculate the number of bacteria per cell. After optimising the experiment conditions, the chosen MOI was 100 to be able to visualise Salmonella-macrophage interaction. For the functional importance of PARPs, a concentration of 50 µM was chosen for PJ34 because higher concentrations were causing interference in flowcytometry with the SL-1344-GFP signal. Results from flowcytometry revealed that during salmonellosis, PJ34 treatment showed more cells associated with bacteria than non-treated cells at 6 hours, yet this difference was not significant indication that PJ34 has no major effects on salmonellosis. Epifluorescence microscopy showed the heterogenous nature of infection that is characterised by the different number of bacteria per infected cell.
Keywords: Salmonella, ADP-ribosylation, PJ34, PARPs, salmonellosis, imaging